STRATEGI PENINGKATAN EKONOMI MASYARAKAT MELALUI PEMBERDAYAAN UMKM DI ERA EKONOMI DIGITAL (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
MSME are independent companies that have great potential in improving people's welfare. The era of the digital economy is a great opportunity for MSME to develop due to the opening of access to information for MSME. But MSME are in villages which are often constrained by the development of the digital economy, especially digital technology. The purpose of community service in the accounting study program is to provide knowledge and assistance for MSME in dealing with the digital economy so that MSME can survive and develop. The community service method is through knowledge transfer and mentoring. The result of community service is the addition of MSME actors' knowledge in Pagenteran Village about the digital economy in MSME management, both marketing, finance and product innovation